Ultrasonographic Signs of Cytomegalovirus Infection in the Fetus—A Systematic Review of the Literature - Magda Rybak-Krzyszkowska; Joanna Górecka; Hubert Huras; Magdalena Staśkiewicz; Adrianna Kondracka; Jakub Staniczek; Wojciech Górczewski; Dariusz Borowski; Mariusz Grzesiak; Waldemar Krzeszowski; Magdalena Massalska-Wolska; Renata Jaczyńska (Diagnostics, 2023)
Background: congenital cytomegalovirus (cCMV) infection during pregnancy is a significant risk factor for fetal and neonatal morbidity and mortality. CMV detection is based on the traditional ultrasound (US) and MRI (magnetic resonance) approach. Methods: the present review used the PRISMA protocol for identification of studies associated with CMV infection and sonographic analysis. Various search terms were created using keywords which were used to identify references from Medline, Pubmed, PsycInfo, Scopus and Web of Science. Results: sonographic analysis of the cCMV infection identified several of the key features associated with fetuses. The presence of abnormal patterns of periventricular echogenicity, ventriculomegaly and intraparenchymal calcifications is indicative of CMV infection in the fetus. Hyperechogenic bowels were seen frequently. These results correlate well with MRI data, especially when targeted transvaginal fetal neurosonography was carried out. Conclusions: ultrasonography is a reliable indicator of fetal anomalies, due to cCMV. Fetal brain and organ changes are conclusive indications of infection, but many of the ultrasonographic signs of fetal abnormality could be due to any viral infections; thus, further research is needed to demarcate CMV infection from others, based on the ultrasonographic approach. CMV infection should always be an indication for targeted fetal neurosonography, optimally by the transvaginal approach.